Tantangan dan Peluang Bisnis Dalam Pengembangan Kewirausahaan di Sektor Kemaritiman - M.Tegar Ramadhani S.P; Laily Aprilia Maulina; Christian Simanjuntak; Ghali Ravzanjani Novandi; Denny Oktavina Radianto (Lembaga Pengembangan Kinerja Dosen, 2024)
Social media has become an essential tool in the development of Micro, Small, and Medium Enterprises (MSMEs) in this digital era. This research aims to investigate the role of social media in supporting the growth and success of MSMEs. Through a comprehensive literature review, this study explores the various benefits obtained by MSMEs from the use of social media, including increased visibility and market reach, more intensive customer interactions, and enhanced brand awareness and business image. However, this research also identifies several challenges faced by MSMEs in leveraging social media, including limitations in digital knowledge and skills, as well as managing limited time and resources. Based on these findings, this study concludes that it is important for MSMEs to equip themselves with the necessary digital knowledge and skills, and to develop targeted and sustainable marketing strategies through social media. Additionally, support from government and non-profit organizations in the form of training, resources, and technical assistance can also help MSMEs harness the full potential of social media for their business growth. By overcoming these challenges, MSMEs can maximize the benefits of social media in supporting the growth and success of their businesses in an increasingly digital market.